Parkinson's disease and comorbid myasthenia gravis: a case report and literature review - Zhang, Qihao; Xu, Erhe; Li, Hai-Feng; Chan, Piu; Zhao, Zhenzhen; Ma, Jinghong (Frontiers in Neurology, 2024)
Background: Parkinson's disease (PD) is the second most common neurodegenerative disease after Alzheimer's disease. Myasthenia gravis (MG) is a rare autoimmune disease, which is caused by antibodies against the neuromuscular junction. PD and comorbid MG are rare to be seen.Case presentation: Here we report a patient who was diagnosed with PD and MG. A 74-year-old male had a 4-year history of bradykinesia and was diagnosed with PD. He subsequently developed incomplete palpebral ptosis, apparent dropped head, and shuffling of gait. His results of neostigmine tests were positive. Repetitive nerve stimulation (RNS) showed significant decremental responses at 3 and 5 Hz in the orbicularis oculi. His anti-acetylcholine receptor antibody (anti-AchR antibody) serum level was also elevated. Meanwhile, 9-[ 18 F]fluoropropyl-(+)-dihydrotetrabenazine positron emission tomography-computed tomography ( 18 F-AV133 PET-CT) scan revealed a significant decrease in uptake of bilateral putamen. After adding cholinesterase inhibitors, his symptoms of palpebral ptosis and head drop improved greatly and he had good response to levodopa.Though PD with MG is rare, we still need to notice the possibility for a PD patient to have comorbid MG. The underlying mechanism of PD and comorbid MG remains unknown. The imbalance between neurotransmitter dopamine and acetylcholine, and the immune system are likely to play significant roles in the pathogenesis. In this article, we will present our case and a literature review about the co-occurrence of PD and MG to review their clinical features, and discuss the underlying pathogenesis mechanism of this comorbidity.